AB1411 Anatomical basis of rheumatologic examination: Upper extremity and cervical region. (23rd January 2014) - Villaseñor-Ovies, P.; Saavedra, M.A.; Biundo, J.; Kalish, R.A.; Canoso, J.J.; de Toro-Santos, F.J.; Carette, S.; Hernández-Díaz, C.; McGonagle, D.; Navarro-Zarza, J.E.
Abstract : Background: The rheumatologic examination, which is based on a sound internal medicine examination, focuses predominantly on the musculoskeletal system. However, seasoned rheumatologists recognize the importance of the neurologic and vascular examination as well. Objectives: The current survey is a group effort at listing musculoskeletal, neural and vascular structures that may be most relevant to a successful training in, and practice of, rheumatology. Methods: The Mexican Task Force on Clinical Anatomy (GMAC) is an officially recognized group of the Mexican College of Rheumatology that is comprised of 6 rheumatologists (one off site, RAK) who have had extensive training in clinical anatomy, combined training sessions with the Mexican School of Ultrasonography and anatomists of the National University of Mexico (UNAM), as well as intragroup certification in clinical anatomy. Members of this group individually listed anatomical items felt to be relevant to the practice of rheumatology. A final items list was circulated to the GMAC members and 4 internationally recognized rheumatologists for a Delphi exercise. Items were rated as unimportant, fairly important, moderately important, important and very important. Consensus was reached when an item was rated important or very important by 8 or more of the 10 participants. The original list went through 2 Delphi rounds and consensus items were subsequently analyzed according to the structure involved, anatomical region and possibility of identification on physical examination. Results: The initial list had 549 items including 381 (69.3%) musculoskeletal (bone, joint, ligament, tendon, enthesis, fascia, bursa), 75 (13.6%) neural, 14 (2.5%) vascular and 75 (13.6%) classified as other. At the 1st Delphi round consensus was reached in 129 items and at the 2nd round 92 consensus items were added reaching a total of 221 (40.2%) items. Of these 125 (56.5%) were musculoskeletal, predominantly muscles (47), joints (27), bones (23) and tendons (17). Of the items that reached consensus, 62 (28%) pertained to the hand, 53 (23.9%) to the shoulder, 45 (20.3%) to the cervical spine and 43 (19.4%) to the elbow. Finally, 103 (46.6%) items were considered identifiable on physical examination. Conclusions: Given our interest in clinical anatomy our initial listing was, if anything, over-inclusive. However, most of the participants in this exercise are practicing rheumatologists and it was our hope that our collective experience would be reflected in the findings. While musculoskeletal items understandably prevailed a surprisingly high number of neural items were considered important. This should not be unexpected given the intricate anatomical and clinical relations between both systems. Disclosure of Interest: None Declared